Perbandingan Penerapan Metode Pembelajaran Buzz Group dan Metode Ceramah Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas XII IPA di SMAN 2 Muaro Jambi - Nuraini, Risfa Andriani; Rosmiati; Mayasari (JPEAKU (Jurnal Pendidikan Ekonomi Akuntansi Kewirausahaan), 2024)
This study aims to describe the comparison of the application of buzz group learning methods and lecture methods to the learning outcomes of grade XII science students in economics subjects at SMAN 2 Muaro Jambi. This research is a quantitative approach with an experimental type of research using a Quasi Experimental Design design with a non-equivalent control group design model. The population used in this study was class XII science consisting of 2 classes while the sample in this study was students of class XII science 2 as an experimental class taught with the buzz group learning method and XII science 3 as a control class taught by the lecture method. Research data were obtained by providing pretest and posttest. Based on the results of data analysis, calculation, and discussion, the average value of experimental class learning outcomes before the application of the buzz group method was 62.40 and after the application of the method was 68.90. As for the control class, the average value of the learning outcomes of the control class before the application of the method was 56.30 and after the application of the method was 49.63. In addition, based on the output results, a calculated t value of 2.692 was obtained with a confidence level of 95% (α = 5%) df = (57) for testing obtained a table t value of 2.002 from the calculation, it can be seen that the calculated t value is greater than the table t with a Sig value. (2-tailed < Alpha (0.009 < 0.05), then H 03 is rejected and H a3 Accepted. This means that there is a significant comparison between the experimental posttest and the control posttest